Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's analyze and simplify the given equation step-by-step to determine which standard form of the equation of a parabola it becomes.
Given the equation:
[tex]\[ \sqrt{(x-0)^2 + (y-p)^2} = \sqrt{(x-x)^2 + (y-(-p))^2} \][/tex]
First, we can simplify it:
[tex]\[ \sqrt{x^2 + (y-p)^2} = \sqrt{(y+p)^2} \][/tex]
Simplifying the right-hand side:
[tex]\[ \sqrt{x^2 + (y-p)^2} = |y+p| \][/tex]
We need to consider the absolute value because it represents the distance, which is always positive. The general understanding here will follow:
[tex]\[ \sqrt{x^2 + (y-p)^2} = |y+p| \][/tex]
Now let's square both sides to eliminate the square roots:
[tex]\[ x^2 + (y-p)^2 = (y+p)^2 \][/tex]
Expanding both sides:
[tex]\[ x^2 + y^2 - 2py + p^2 = y^2 + 2py + p^2 \][/tex]
Subtracting [tex]\(y^2 + p^2\)[/tex] from both sides, we get:
[tex]\[ x^2 - 2py = 2py \][/tex]
Combining like terms:
[tex]\[ x^2 - 4py = 0 \][/tex]
Thus we have the final simplified equation:
[tex]\[ x^2 = 4py \][/tex]
Therefore, the equation of the parabola [tex]\( \sqrt{(x-0)^2 + (y-p)^2} = \sqrt{(x-x)^2 + (y-(-p))^2} \)[/tex] simplifies to [tex]\( x^2 = 4py \)[/tex].
So, the correct option is:
[tex]\[ x^2 = 4py \][/tex]
Given the equation:
[tex]\[ \sqrt{(x-0)^2 + (y-p)^2} = \sqrt{(x-x)^2 + (y-(-p))^2} \][/tex]
First, we can simplify it:
[tex]\[ \sqrt{x^2 + (y-p)^2} = \sqrt{(y+p)^2} \][/tex]
Simplifying the right-hand side:
[tex]\[ \sqrt{x^2 + (y-p)^2} = |y+p| \][/tex]
We need to consider the absolute value because it represents the distance, which is always positive. The general understanding here will follow:
[tex]\[ \sqrt{x^2 + (y-p)^2} = |y+p| \][/tex]
Now let's square both sides to eliminate the square roots:
[tex]\[ x^2 + (y-p)^2 = (y+p)^2 \][/tex]
Expanding both sides:
[tex]\[ x^2 + y^2 - 2py + p^2 = y^2 + 2py + p^2 \][/tex]
Subtracting [tex]\(y^2 + p^2\)[/tex] from both sides, we get:
[tex]\[ x^2 - 2py = 2py \][/tex]
Combining like terms:
[tex]\[ x^2 - 4py = 0 \][/tex]
Thus we have the final simplified equation:
[tex]\[ x^2 = 4py \][/tex]
Therefore, the equation of the parabola [tex]\( \sqrt{(x-0)^2 + (y-p)^2} = \sqrt{(x-x)^2 + (y-(-p))^2} \)[/tex] simplifies to [tex]\( x^2 = 4py \)[/tex].
So, the correct option is:
[tex]\[ x^2 = 4py \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.